Peranan Penggunaan Fiskal Desa terhadap Kemiskinan Pedesaan di Kabupaten Jombang - Chyntia Ersa Varina; Teguh Hadi Priyono; Fajar Wahyu Prianto; Sunlip Wibisono (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
Poverty is one of the main problems in both developed and developing countries. Various factors that can cause poverty include low investment levels, slow economic growth, uneven infrastructure development, ineffective government spending on poverty alleviation programs. The government has not been effective in allocating the APBN or APBD in the poverty program so that poverty still cannot be overcome. As we know that poverty is one of the conditions discussed by the community, one of which is in Jombang Regency. The purpose of this study was to determine the role of village fiscal on poverty that occurred in Jombang Regency. This type of research is explanatory research with secondary data type in the form of panel data consisting of time series data for 2010-2019 and cross-section data of 8 villages in Jombang Regency. Analysis of the data in this study using Multiple Regression. The test results of this study indicate that the APBDes Infrastructure budget has a negative and significant effect on poverty in Jombang Regency. Poverty subsidy APBDes has a negative and significant effect on poverty in Jombang Regency. While the BUMDES economic APBDes has a positive effect on poverty. The influence of the independent variable on the dependent variable has an effect of 99.99% as well as a measure of the success rate of regression in predicting the value of the independent variable on the dependent. Keywords: Poverty, APBDes, Panel Data Regression